Analisis Teknik Terjemahan Pengurangan dan Penambahan dalam Buku Menu Restoran di Situs Traveloka - Mulan Maulinda Pratiwi; Lusi Susilawati; Ramdan Sukmawan (Penaoq: Jurnal Sastra, Budaya dan Pariwisata, 2021)
English has become an international language where everyone can communicate in one language. Along with the development of the times and today's technology makes it easier for people to access anything and anywhere. This phenomenon has an impact on the economic sector, especially in the culinary business, not a few culinarybusinessman use English and Indonesian in their menus to make it easier for local and foreign customers. It is undeniable that translating food menus is not an easy task where the target language must deliverd information well from the source language. the translation process is not easy, frequent errors such as omission or addition of words make the information not deliverd well, making researchers find two problem formulations, namely how to omit and add translation techniques in menu restaurant on the Traveloka site. This study aims to identify and classify omission and addition translation techniques. This study used descriptive qualitative method. the results of this study there are 4 types of omission and addition, namely the omission of nouns (9), omission of noun phrases (3), omission of adjectives (9), omission of adverbs (3), addition of nouns (11), addition of noun phrases (6), addition of adjectives (18) and addition of conjunctions (9).